Can Strategy Address the Climate Crisis Without Losing its Essence? - Davis, Gerald F.; DeWitt, Theodore (Journal of Management Studies, 2025)
AbstractHow should academic fields take on the existential risks created by the climate crisis? What can business schools do to accelerate the decarbonization of business required to save our species? In their Point, Bansal et al. argue that the field of strategic management is complicit in bringing about our current crisis, and they propose to reformulate the field's very foundations to help get us out. In our Counterpoint, we show why we agree with the diagnosis but argue why we are sceptical of the cure. Strategic management incubated in business schools devoted to creating shareholder value, and its central frameworks commit it to this mission, making it fundamentally impossible to reform. The adjustments suggested by Bansal et al. might nudge what is published in journals but will not solve the bigger challenge. If we are to turn back from the climate disaster and begin the process of mitigation and remediation, we need to equip firms to decarbonize their operations as quickly as possible, and to create new kinds of enterprise to bring about the clean energy transition. Given its history and methods, organization theory may be better equipped to take on this role.